Introduction - Karapanos, Evangelos (My University, 2013)
48% of returned products are not attributed to a violation of product specifications (Den Ouden et al., 2006). This finding was the initial motivation for this research project. Brombacher, den Ouden and colleagues (e.g., Den Ouden et al., 2006; Brombacher et al., 2005; Koca et al., 2009) found that an alarmingly increasing number of returned products, in 2002 covering 48% of returned products, are technically fully functional, i.e. according to specifications, but they are returned on the basis of failing to satisfy users' true needs (28%), or purely because of users' remorse (20%) (Den Ouden et al., 2006). Brombacher et al. (2005) introduced the term 'Soft Reliability' to refer to these situations where in spite of meeting with the explicit product specifications, a customer explicitly complains on the (lack of) functionality of the product.
Keywords: User Experience; Interactive Product; Perceptual Judgment; Personal Relevance; Evaluative Judgment